TEACHERS' EFFORTS TO IMPROVE CHILDREN'S LANGUAGE SKILLS THROUGH ROLE PLAYING ACTIVITIES AT RA INTISYARUL ULUM - Infik Ivadatun Qomariah; Aisyah Bashiratul Mahiroh; Magnolia Nerelina Puspa; Vike Nurjannah; Agustiarini Eka Dheasari (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to describe teachers' efforts in improving children's language skills through role-playing activities at RA Intisyarul Ulum. The study used a descriptive qualitative approach with 20 children in group A as subjects. Data collection techniques included observation, interviews, and documentation, while data analysis used the Miles and Huberman model. The results showed that role-playing activities were effective in developing children's language skills, especially in the aspects of speaking courage, sentence fluency, vocabulary mastery, and listening skills. The role of teachers as facilitators was proven to help create communicative, interactive, and enjoyable learning so that children were more active in participating. Thus, role-playing can be used as a relevant and effective learning strategy in improving the language skills of early childhood